2017
DOI: 10.1021/acsnano.7b03226
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging-Guided Photothermal/Photoacoustic Synergistic Therapy with Bioorthogonal Metabolic Glycoengineering-Activated Tumor Targeting Nanoparticles

Abstract: Developing multifunctional phototheranostics with nanoplatforms offers promising potential for effective eradication of malignant solid tumors. In this study, we develop a multifunctional phototheranostic by combining photothermal therapy (PTT) and photoacoustic therapy (PAT) based on a tumor-targeting nanoagent (DBCO-ZnPc-LP). The nanoagent DBCO-ZnPc-LP was facilely prepared by self-assembling of a single lipophilic near-infrared (NIR) dye zinc(II)-phthalocyanine (ZnPc) with a lipid-poly(ethylene glycol) (LP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(110 citation statements)
references
References 75 publications
1
109
0
Order By: Relevance
“…The photoacoustic (PA) shockwave, created by the cavitation (growth and collapse) of nanobubbles and microbubbles around nanoparticles heated by laser pulses, produces a strong and localized mechanical disruption of the tissue it comes into contact with . Our previous studies have demonstrated that a PA shockwave can be effective in producing localized cytotoxicity in nanoparticle‐targeted cells . The application of a nanoparticle activated by a pulsed laser to produce a PA shockwave is referred to as PA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The photoacoustic (PA) shockwave, created by the cavitation (growth and collapse) of nanobubbles and microbubbles around nanoparticles heated by laser pulses, produces a strong and localized mechanical disruption of the tissue it comes into contact with . Our previous studies have demonstrated that a PA shockwave can be effective in producing localized cytotoxicity in nanoparticle‐targeted cells . The application of a nanoparticle activated by a pulsed laser to produce a PA shockwave is referred to as PA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Unsurprisingly, glycoengineering represents an enabling technology for various biomedical applications, namely, both live cell, and extracellular vesicle labeling/tracking, drug‐based cancer theranostics, as well as cell‐based chemo‐ and immunotherapies . Despite an impressive body of literature on these recent advances, tissue engineering concepts exploiting this biomachinery phenomenon are still at their youth.…”
Section: Cell‐rich Assembliesmentioning
confidence: 99%
“…Recently, several probes including photosensitizers (PSs) and photoacoustic agents that combine imaging and therapeutic functions have been introduced to tumors for imaging or image‐guided therapy based on bio‐orthogonal labeling . Owing to intrinsic signals from the probes, it is almost not possible to differentiate the target, such as tumors from normal organs or tissues during the initial several hours upon probe administration.…”
Section: Figurementioning
confidence: 99%